Rapid and accurate identification of Staphylococcus species by tRNA intergenic spacer length polymorphism analysis. - Maes, N (1997)
PCR-amplified tRNA gene (tDNA) intergenic spacer length polymorphism (tDNA-ILP) was analyzed for its ability to identify to the species level type strains (n = 18) and clinical isolates (n = 163) of staphylococci. Amplified products obtained by PCR with outwardly directed consensus tDNA primers were separated by agarose and polyacrylamide gel electrophoreses. The results were compared with those obtained by biochemical identification and ribotyping. Each type strain presented a specific tDNA-ILP pattern. PCR with fluorescent primers allowed for the detection of labelled DNA fragments on polyacrylamide gels by using an automated laser fluorescence sequencer and provided enhanced pattern resolution in comparison with that by analysis on agarose gels. tDNA patterns indistinguishable from those of the type strains were produced by clinical isolates of all tested species except for some isolates of S. aureus (n = 3) and S. haemolyticus (n = 1), which showed variant patterns. Strains of S. saprophyticus and S. xylosus showed very closely related profiles, and S. cohnii subspecies were indistinguishable. The identities obtained by tDNA-ILP analysis agreed with those obtained by the biochemical method to the species level for 99% (162 of 163) of the strains tested and to the subspecies level for 96% (156 of 163) of the strains tested. These results indicate that fluorescence-labelled PCR analysis of tDNA-ILP provides an accurate and rapid molecular method for the identification of human staphylococci.